The Comprehensive Development Framework - Wolfensoh, James D. (World Bank, Washington, DC, 2020)
Just over a year ago, on January 21, 1999, the authors circulated a proposal for a Comprehensive Development Framework (CDF), a discussion draft. The response has been overwhelmingly supportive. By way of illustration, in September 1999, the development assistance committee of the Organization for Economic Cooperation and Development (OECD) prepared 'on common ground', a paper which reflects the consensus reached in the international development community on the CDF's main tenets. Another sign of this growing consensus is the recent endorsement by the Governors of the World Bank Group and International Monetary Fund (IMF) of CDF principles as the basis for poverty reduction strategies for developing countries seeking Bank or International Monetary Fund (IMF) assistance, or debt relief under the Highly Indebted Poor Country Initiative (HIPC). As the international development community accepts the CDF as the approach to development which complements the necessary macroeconomic growth strategy without which poverty reduction cannot be achieved, the CDF is evolving from a Bank proposal into a widely used tool.